PUBLIC RESPONSE TO CELEBRITY SUICIDES NEWS DUE TO MENTAL HEALTH ISSUES - Anisa Rizki Titania (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2022)
Around 800,000 people die by suicide in a year, or one per 40 seconds. Despite the fact that suicide is a complex phenomenon impacted by personal qualities as well as numerous socioenvironmental factors, it is considered as a avoidable public health problem, and public health methods to suicide prevention are fast gaining traction. Because of its vast impact, media might be considered to have a